Tasting the Port Wine Cellar experience: what features please the most? - Rita, P.; Moro, S. (Journal of Wine Research, 2022)
This study addresses wine tasting experienced by tourists in the context of the worldwide renowned Port wine. A total of 824 online reviews posted about four major Port wine cellars in TripAdvisor were collected. Data were analyzed with text mining and topic modeling, and sentiment scores, as well as ratings, were also considered. Overall, results showed that guests were primarily attracted by the experience as a whole, including the tour and the wine culture and not just the wine tasting experience. Furthermore, six topics were found with associated main keywords and comprehending distinct groups of guests with different preferences. Three groups underlined tour and visiting experience, whereas two other groups were composed of enthusiastic wine fans, with one more focused on the wine/winery/cellar experience while the other enjoyed a diversified wine selection. Yet another group aggregated tourists who valued the food experience.